The Life and Times of Mary Musgrove - Hahn, Steven C. (Book collections on Project MUSE., 2012)
The story of Mary Musgrove (1700-1764), a Creek Indian-English woman struggling for success in colonial society, is an improbable one. As a literate Christian, entrepreneur, and wife of an Anglican clergyman, Mary was one of a small number of "mixed blood" Indians to achieve a position of prominence among English colonists. Born to a Creek mother and an English father, Mary's bicultural heritage prepared her for an eventful adulthood spent in the rough and tumble world of Colonial Georgia Indian affairs. Active in diplomacy, trade, and politics--affairs typically dominated by men--Mary work